2021
DOI: 10.18870/hlrc.v11i0.1218
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study Examining Home as Faculty Workplace During COVID-19 Self-Isolation

Abstract: Objectives: Using the lens of the virtual workplace model, the current basic qualitative study examined how COVID-19 self-isolation affected both online and land-based faculty (working online as an emergency due to COVID-19) workspaces and work processes. Method: A total of 20 online and six land-based faculty completed e-mail interviews both one month and 3 months post self-isolation. Results: Online faculty were more satisfied with their home workplace, but both groups felt more negative about their online w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Stadtlander and Sickel conducted interviews with university faculty and found that whilst staff were generally satisfied with their home workplace, they felt more negative about online work and a loss of freedom and independence. The authors noted that some staff experienced an increase in their working hours as a result of the transition to online working, with some feeling overwhelmed by this transition [42]. The current study purposively sampled staff in student-facing roles from a variety of role families to represent the make-up of the university workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Stadtlander and Sickel conducted interviews with university faculty and found that whilst staff were generally satisfied with their home workplace, they felt more negative about online work and a loss of freedom and independence. The authors noted that some staff experienced an increase in their working hours as a result of the transition to online working, with some feeling overwhelmed by this transition [42]. The current study purposively sampled staff in student-facing roles from a variety of role families to represent the make-up of the university workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Reported benefits from working from home (WFH) included reducing work-family conflict and role overload [ 2 ]; lower worker stress levels, improved health and reduced absence from work [ 3 , 5 ]; reduced depression levels in mothers of young children [ 4 ]; improved quality of life [ 6 ]. However such benefits had not been demonstrated consistently across different workforce and contexts, and in some cases WFH in general had been found to have negative consequences [ 7 10 ]. Studies report that WFH were not always necessarily beneficial to employees in terms of social, behavioural and physical factors [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research showed that it might impact workers’ creativity and opportunities to seek help and support, the management relationships, in particular on opportunities for feedback, learning & performance management [ 11 ]. Feeling stressed due to self-isolation, which in turn could affect their feelings about work [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research that specifically examines the impact of COVID-19 on higher education explores how workers have adjusted to the COVID-19 workplace, including professional services staff (e.g., Watermeyer et al, 2022), learning technologists (Watermeyer et al, 2021) and academics (Karatuna et al, 2022;Kennedy, Oliver & Littlejohn, 2022;McGaughey et al, 2021;Rode, Kennedy & Littlejohn, 2022;Stadtlander & Sickel, 2021). Almost universally noting increased workloads, these studies nonetheless tend to focus on cultural and organisational change rather than how information practices have adjusted through the shift to online and hybrid employment.…”
Section: The Work Of Higher Educationmentioning
confidence: 99%